English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

A. 2x^2 - 6 = ( 2x+ 3)(x - 2)
B. 2x^2 + x-6 = (2x - 2) (x + 3)
C. 2x^2 - 11x - 6 = (2x + 1) ( x - 6)
D. 2x^2 +11x - 6 = (2x - 1) (x +6)

" - " This means subtraction.

2007-01-11 15:48:11 · 8 answers · asked by Lizzie 5 in Science & Mathematics Mathematics

8 answers

A & B.

Remember: First, Outer, Inner, Last (FOIL)

First: 2x*x = 2^2
Outer: 2x*-2 = -4x
Inner: 3*x = 3x
Last: 3*-2 = -6

So: 2^2 - 4x + 3x - 6 = 2^2 - x - 6

First: 2x*x = 2^2
Outer: 2x*3 = 6x
Inner: -2*x = -2x
Last: -2*3 = -6

So: 2^2 + 6x - 2x - 6 = 2^2 + 4x - 6
.

2007-01-11 15:52:43 · answer #1 · answered by Johhny Drama 5 · 1 0

A. is the incorrect answer.
The RHS of the equation = 2x^2 -x-6 which is certainly not equal to 2x^2-6

2007-01-11 23:55:38 · answer #2 · answered by ironduke8159 7 · 0 0

A and B are not true., because
A is
2x^2 - 6
=2(x^2 - 3)
=2(x + sqroot3)(x - sqroot3)

and, B is
2x^2 + x - 6
= 2x^2 + 4x - 3x - 6
= 2x(x + 2) - 3(x + 2)
= (x + 2)(2x - 3)

Hence, both A and B are incorrect.

2007-01-12 00:06:05 · answer #3 · answered by rishi 2 · 1 0

A and B.

A. (2x+ 3)(x - 2) = 2x^2 - 4x + 3x - 6 = 2x^2 - x -6

B. (2x - 2) (x + 3)= 2x^2 +6x - 2x - 6 = 2x^2 +4x -6

2007-01-11 23:53:31 · answer #4 · answered by Jerry P 6 · 1 0

A RHS = 2x^2 -4x + 3x - 6
B RHS = 2x^2 + 6x - 2x - 6
c RHS = 2x^2 - 11x + x -6
d RHS = 2x^2 + 11x - x - 6

SO......A and B

2007-01-11 23:57:16 · answer #5 · answered by Anonymous · 1 0

a is false because if you foil the right side there would be a -x term

b is false because the coefficent of x should be 4, not 1

c is true
d is true

2007-01-11 23:54:27 · answer #6 · answered by Anonymous · 1 0

A.
B.

Verify by using FOIL method.

2007-01-11 23:57:20 · answer #7 · answered by S. B. 6 · 1 0

??????????????????????????????????????????

2007-01-12 11:25:53 · answer #8 · answered by Anonymous · 0 0

fedest.com, questions and answers